Genotyping of individual Ceratonova shasta (Cnidaria: Myxosporea) myxospores reveals intra-spore ITS-1 variation and invalidates the distinction of genotypes II and III. Issue 12 (27th March 2018) - Atkinson, Stephen D.; Hallett, Sascha L.; Bartholomew, Jerri L.
Abstract: Genotypes of the myxosporean parasite Ceratonova shasta are defined by the number of ATC repeats in the parasite's ribosomal DNA internal transcribed spacer region 1. These genotypes correlate with specific salmonid fish hosts. We observed coho salmon ( Oncorhynchus kisutch ) and rainbow trout ( Oncorhynchus mykiss ) with mixtures of genotypes II and III, and assumed that this was a consequence of fish having an aggregate infection from multiple individual parasites. We hypothesized that although multiple ITS copies are present within a parasite spore, the DNA sequences of these copies are identical, and thus individual C. shasta spores are a single genotype. We tested this by extracting and sequencing DNA from individual myxospores. We trialed three approaches for in-tube DNA extraction; digestion with proteinase K was superior to simply rehydrating spores, or incubation in the buffer. Sequences from 14 myxospores were each a mixture of genotypes II and III. Therefore, intra-genomic ribosomal DNA variants exist within individual parasite spores, and II and III should no longer be regarded as discrete C. shasta genotypes. This single-spore genotyping approach will be a useful tool for testing validity of other C. shasta genotypes, and for correctly matching genotype with phenotype for mixed infections of other myxozoan species.